Implementasi Pembelajaran Fisika Topik Usaha dan Energi Berdasarkan Publikasi Ilmiah - Pinky Ersa Niyanti; Fitria Putri Setyaningrum; Gustama Wibawa Rachman; Fidelia Wandita (Mitra Pilar: Jurnal Pendidikan, Inovasi, dan Terapan Teknologi, 2022)
AbstractWork and energy is one of the important physics learning topics. Learning physics, especially on the topic of work and energy, can be done using various learning methods and media, the results of which will certainly be different for each learning method and media used. Therefore, the purpose of this paper is to find out the various models and learning media and their effects used in learning on the topic of work and energy. This research was examined through the meta-analysis method by collecting data from research literature studies of the same theme. The results obtained in this study were as many as 36 journals on learning physics on the topic of work and energy. This study concludes that learning media methods that can be applied in the process of learning effort and energy include the Learning Cycle 7E method, STEM, Problem Solving, Think-Pair-Share, Inquiry, Critical Thinking Skills, Predict Observe Explain (Poe), Project Based Learning, Certainty Of, Response Index (CRI), Multiple Representations, ARCS, Flipped Classroom, Problem-Based Learning (PBL), Inquiry-STEM, Scientific Communicating Skills, Online Hybrid Learning, and Creative Thinking Skills. And learning media that can be used in business and energy learning include Matlab, C-Map, PhET, E-Module, Android Smartphone-Based Online Tests, Student Worksheets, Kokami media, Lectora Inspire, Macromedia Director, Schoology, Andro-Web Comics, and Macromedia Flash. AbstrakUsaha dan energi merupakan salah satu topik pembelajaran fisika yang penting. Pembelajaran fisika, khususnya pada topik usaha dan energi ini dapat dilakukan dengan berbagai metode dan media pembelajaran, yang mana hasilnya pasti akan berbeda di setiap metode dan media pembelajaran yang digunakan. Oleh karena itu, tujuan dibuatnya tulisan ini adalah untuk mencari tahu berbagai model dan media pembelajaran serta pengaruhnya yang digunakan pada saat pembelajaran pada topik usaha dan energi. Penelitian ini dikaji melalui metode meta analisis dengan mengumpulkan beberapa data dari studi literatur penelitian yang setema. Hasil yang didapakan pada penelitian ini yaitu sebanyak 36 jurnal tentang pembelajaran fisika pada topik usaha dan energi. Kesimpulan pada penelitian ini yaitu didapatkan bahwa media metode pembelajaran yang dapat diterapkan dalam proses pembelajaran usaha dan energi diantaranya adalah metode Learning Cycle 7E, STEM, Problem Solving, Think-Pair-Share, Inkuiri, Critical Thinking Skills, Predict Observe Explain (Poe), Project Based Learning, Certainty Of, Response Index (CRI), Multiple Representations, ARCS, Flipped Classroom, Problem Based Learning (PBL), Inquiry-STEM, Scientific Communicating Skills, Online Hybrid Learning, dan Creative Thinking Skills. Dan media pembelajaran yang dapat dipakai pada pembelajaran usaha dan energi diantaranya Matlab, C-Map, PhET, E-Modul, Online Test Android Smartphone Based, Student Worksheet/Lembar Kerja Siswa, Kokami media, Lectora Inspire, Macromedia Director, Schoology, Andro-Web Comics, dan Macromedia Flash.